Analisa Kejadian Stunting Dengan Tingkat Perkembangan Balita Usia 36-48 Bulan - Sitti Zakiyyah Putri; Sitti Maryam Bachtiar; Dahniar; Ismul (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Stunting is a nutritional status that is based on the Body Height index by Age (TB / U). The incidence of stunting that has taken place since childhood has a very strong relationship with slow motor and IQ (intelligence) is lower. The level of development of children has a higher quality than normal resources this has increased cognitive levels, poor learning and psychosocial achievement. The purpose of this study is to see whether there is a relationship between stunting events and the level of development of toddlers aged 36-48 months in TK Pertiwi Majene 2019. This type of research is observational analytic research with a cross-sectional study with the method of Exhaustive Sampling and the instruments used are microtome and graphs used. used as a KPSP questionnaire developmental level questionnaire. The sample used was toddlers aged 36-48 months as many as 38 people. The results of the analysis approved by Chi-Square showed rejected with a significant value of 0.37, which means greater than 0.05 (p> 0.05). It is possible to conclude that there is a significant relationship between the incidence of stunting with the level of development of toddlers aged 36-48 months. Suggestions for further researchers to be able to add factors that can influence the occurrence of stunting as well as adding samples to get more significant results.